Kazachstan jako obecny przewodniczący OBWE – rok 2010: nowa rola średnich państw w podejmowaniu globalnych decyzji strategicznych na podstawie konsensusu - Sydyknazarov, Mukhit (Przegląd Politologiczny, 2018)
The paper concerns the issue of Kazakhstan presiding over the OSCE this year, and the issue of the role played by medium-sized states in the contemporary architecture of international relations. As the interests of global players continue to clash incessantly, medium-sized states are forced to make increased efforts to build a safer and more stable world. The author uses the example of Kazakhstan to analyze the role of medium-sized states, which can be compared to that played by small and medium-sized enterprises in building an efficient and stable economy. The small and medium-sized states are increasingly appreciated on an international scale in various areas. Kazakhstan is consistently working to achieve its goals, not only at present within the OSCE, but as a future head of other organizations, many of which have been established on Kazakhstan’s initiative; the country has always been distinguished by its international activity. Many of these initiatives have been successfully implemented by the OSCE itself. The above-mentioned organizations include the Conference on Interaction and Confidence Building Measures in Asia (CICA), Shanghai Cooperation Organization (SCO), Eurasian Economic Community (EurAsEC), Organization of the Islamic Conference (OIC), International Organization of Turkic Culture, and the Permanent Council of Ministers of Culture of the International Organization of Turkic Speaking States (TURKSOY). It is important to include the new independent states in the common ideology of the development of market economies and democratic institutions. As a regional leader in Central Asia, Kazakhstan is better prepared to implement this mission than other states. Not all Kazakhstan’s initiatives fall within a purely European framework. As the country is located at the cusp of Europe and Asia, its government pays constant attention to Euro-Asian issues, all the more so as, after its presidency of the OSCE, Kazakhstan will chair the Organization of the Islamic Conference in 2011.